Printing and dyeing wastewater treatment process based on advanced oxidation technology

Through the printing and dyeing wastewater treatment process based on advanced oxidation technology, using technical means such as flocculant composition and Fenton reagent, the problem of poor treatment effect of printing and dyeing wastewater in the prior art has been solved, and efficient removal of organic pollutants and colorimetrics has been achieved, and treatment costs and environmental pressure have been reduced.

CN119797695APending Publication Date: 2025-04-11HANGZHOU XIAOSHAN SILK & CHEM FIBRE PRINTING & DYEING CO
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510240856.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-03
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is poor in treating printing and dyeing wastewater, physical methods cannot achieve essential degradation, chemical methods are prone to secondary pollution, biological methods are harsh and the treatment time is long, making it difficult to effectively remove organic pollutants and color in wastewater.

Method used

The printing and dyeing wastewater treatment process based on advanced oxidation technology is adopted, and the pH value is adjusted to the wastewater, and the anaerobic bacteria treatment and flocculation treatment are carried out. The pollutant is removed using a flocculant composition (polymeric iron sulfate, sodium aluminate, modified diatomaceous earth), and further treated with Fenton reagent and activated carbon filter layer to meet the discharge standards.

Benefits of technology

This process can significantly improve the treatment efficiency of wastewater, achieve efficient removal of organic pollutants, colorimetry and phosphates in printing and dyeing wastewater, reduce chemical oxygen demand (COD) and colorimetry, reduce nitrogen and phosphorus pollution in water, and the process is green and environmentally friendly and has a low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005294087410000111
    Figure BDA0005294087410000111
Patent Text Reader

Abstract

The invention belongs to the technical field of wastewater treatment, and particularly discloses a printing and dyeing wastewater treatment process based on an advanced oxidation technology. Comprising the following steps: (1) adding an acid into the printing and dyeing wastewater to adjust the pH value to 6-7, carrying out anaerobic bacteria treatment, and filtering to obtain a supernatant A; (2) adding a flocculant composition into the supernate A in the step (1), stirring for 4-6 hours, and filtering to obtain supernate B; (3) adding agents, namely a Fenton reagent and alkali liquor, into the supernate B obtained in the step (2), mixing and precipitating, and filtering by using an activated carbon filter layer to obtain supernate C, namely standard discharge water, wherein the adding amount of the Fenton reagent is 0.07-0.08 kg / m < 3 >, and the adding amount of the Fenton reagent is 0.07-0.08 kg / m < 3 >; the flocculant composition is prepared from the following raw materials: polyferric sulfate, sodium aluminate and modified diatomite. The wastewater treatment efficiency is high, residual organic matters and impurities in water can be adsorbed, and more pollutants and chromaticity are removed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of wastewater treatment, and in particular to a printing and dyeing wastewater treatment process based on advanced oxidation technology. Background Art

[0002] Printing and dyeing wastewater refers to the wastewater generated in the production process of the printing and dyeing industry. These wastewaters mainly come from the dyeing, printing, finishing and other processes of textiles. Printing and dyeing wastewater contains a large amount of unreacted dyes, pigments, additives, as well as organic pollutants such as the products after the reaction and the shed materials on the fabric. The wastewater is dark in color and high in chroma. If it is discharged into the nature, it will seriously affect the living environment.

[0003] For the treatment of printing and dyeing wastewater, physical, chemical and biological methods are usually used. The physical method transfers or concentrates the pollutants between phases without essentially degrading the pollutants. The chemical method changes the molecular structure of the pollutants through chemical reactions and degrades them into small molecules. The biological method uses the metabolism of microorganisms to degrade pollutants.

[0004] Among the above treatment methods, simple physical methods cannot meet the treatment requirements, chemical methods are prone to secondary pollution, and biological methods are difficult to implement due to the harsh living conditions of microorganisms, and the time cycle required is relatively long. Therefore, it is urgent to propose a printing and dyeing wastewater treatment process with good treatment effect and green environmental protection to reduce the pressure of printing and dyeing wastewater discharge on the environment. Summary of the invention

[0005] In order to improve the problem of poor treatment effect of printing and dyeing wastewater, the present application provides a printing and dyeing wastewater treatment process based on advanced oxidation technology.

[0006] The present application provides a printing and dyeing wastewater treatment process based on advanced oxidation technology, which adopts the following technical solution: A printing and dyeing wastewater treatment process based on advanced oxidation technology comprises the following steps: (1) adding acid to the printing and dyeing wastewater to adjust the pH to between 6 and 7, performing anaerobic bacteria treatment, filtering, and obtaining a supernatant A; (2) adding the flocculant composition to the supernatant A of step (1), stirring for 4-6 hours, and filtering to obtain a supernatant B; (3) Add Fenton's reagent and alkali solution to the supernatant B of step (2), mix and precipitate for 12-14 hours, and the amount of Fenton's reagent added is 0.07-0.08 kg / m 3 , filter using an activated carbon filter layer to obtain supernatant C, which is the standard discharge water; The raw materials of the flocculant composition are polyferric sulfate, sodium aluminate and modified diatomaceous earth.

[0007] By adopting the above technical solution, the pH value of the wastewater is adjusted to between 6 and 7, which can ensure that anaerobic bacteria are in the most suitable living environment, thereby improving their treatment efficiency. Anaerobic bacteria decompose organic matter in printing and dyeing wastewater under anaerobic conditions and convert it into simpler compounds, thereby achieving the purpose of purifying water quality; it can also convert nitrogen and phosphorus in sewage into a form that is more easily utilized by other microorganisms, which helps to further reduce nitrogen and phosphorus pollution in water bodies.

[0008] A flocculant composition is added to the supernatant A, and the flocculant composition combines with the suspended matter in the printing and dyeing wastewater to form flocs, which are filtered to obtain supernatant B. In the flocculant composition, polyferric sulfate produces a large amount of positively charged iron ions after hydrolysis in water. These iron ions react with negatively charged colloidal particles, suspended matter and some soluble organic matter in the printing and dyeing wastewater to form larger flocs, which settle rapidly under the action of gravity, thereby achieving the removal of pollutants in the wastewater. Polyferric sulfate has a good removal effect on pigments in printing and dyeing wastewater, and its enhanced flocculation can adsorb, bridge and sweep small pigment particles in the water, thereby achieving a high degree of decolorization effect; it can also combine with phosphate ions in the printing and dyeing wastewater to form insoluble iron phosphate precipitates, thereby effectively removing phosphorus.

[0009] There are a large number of hydroxide ions in the molecular structure of sodium aluminate, which can adsorb cations in printing and dyeing wastewater, thereby removing pollutants; and aluminate ions will condense with anions in pollutants to form insoluble precipitates, and then remove pollutants by precipitation. Modified diatomaceous earth itself has high adsorption, large surface area, and large porosity, and can adsorb pollutants such as heavy metals (such as copper, iron, lead, etc.) and organic matter in printing and dyeing wastewater. As an effective adsorbent, diatomaceous earth has a unique structure and purification effect. It can adsorb pigments in printing and dyeing wastewater and effectively remove color; used in combination with polyferric sulfate, it can improve the wastewater treatment effect through synergistic effects.

[0010] The coagulation of polyferric sulfate and sodium aluminate can promote each other, forming more stable and larger flocs and increasing the sedimentation rate; modified diatomaceous earth and polyferric sulfate further enhance the adsorption capacity of printing and dyeing wastewater, which helps to remove more pollutants. Polyferric sulfate, sodium aluminate and modified diatomaceous earth mixed and added to printing and dyeing wastewater can play their respective advantages and synergistically improve the wastewater treatment efficiency.

[0011] The reagents added to the supernatant B are Fenton's reagent and alkali solution. Fenton's reagent can effectively decompose organic matter. Alkali solution is used to adjust the pH so that Fenton's reagent can exert the best effect. Activated carbon filter layer is used for filtration. Activated carbon can absorb residual organic matter and impurities in the water. After filtration, supernatant C is obtained, which is the wastewater that meets the discharge standards.

[0012] Preferably, the mass ratio of the polyferric sulfate, sodium aluminate and modified diatomaceous earth is 1.5-2:1:4-7.

[0013] By adopting the above technical scheme, the mass ratio of polyferric sulfate, sodium aluminate, and modified diatomite is further limited within a certain range, and the treatment effect of the obtained printing and dyeing wastewater is better. Polyferric sulfate ionizes a large amount of iron ions in water, reacts chemically with the dye molecules in the printing and dyeing wastewater or forms floccules that are easy to precipitate through physical adsorption, achieving efficient decolorization of the wastewater, and can oxidize and decompose some organic pollutants in the wastewater, which helps to reduce the chemical oxygen demand (COD); it also forms insoluble metal phosphate precipitation with phosphates in the printing and dyeing wastewater, effectively removing phosphorus from the wastewater. The aluminate ions in sodium aluminate can condense with anionic pollutants in the wastewater to form insoluble precipitates, and then remove the pollutants by precipitation. Modified diatomite has strong adsorption, can adsorb pollutants such as heavy metal ions and organic matter in the wastewater, and has a good adsorption effect on dye molecules.

[0014] The mixed use of polyferric sulfate and sodium aluminate can further enhance the coagulation effect of wastewater and improve the removal rate of pollutants. The synergistic effect of modified diatomite, polyferric sulfate and sodium aluminate can further improve the treatment efficiency of wastewater, and has significant coagulation, decolorization, organic matter removal, phosphorus removal, adsorption and neutralization effects. These effects work together to improve the treatment efficiency and effect of printing and dyeing wastewater and reduce treatment costs.

[0015] Preferably, the method for preparing the modified diatomite comprises the following steps: (1) calcining diatomite at 450-480° C. for 2-3 h, dispersing the diatomite in anhydrous ethanol, adding silane coupling agent KH-550, stirring for 1-2 h, filtering and drying to obtain pretreated diatomite; (2) dispersing the diatomaceous earth pretreated in step (1) in deionized water, adding FeCl3 solution, adjusting the pH value to 1-3 with hydrochloric acid, stirring at 80-85°C for 2-3h, standing for 20-24h, filtering, washing, and obtaining treated diatomaceous earth; (3) Dispersing the treated diatomaceous earth in step (2) in deionized water, adding sodium lignin sulfonate and starch, stirring at a temperature of 60-65° C. for 1-2 h, filtering, and drying to obtain modified diatomaceous earth.

[0016] By adopting the above technical solution, diatomite is calcined at 450-480°C for 2-3h to remove organic matter and moisture in the diatomite, and its pore structure and surface properties may be changed at the same time, thereby improving the subsequent modification effect. The calcined diatomite is dispersed in anhydrous ethanol, and then the silane coupling agent KH-550 is added. The silane coupling agent KH-550 reacts with the hydroxyl groups on the surface of the diatomite to form a chemical bond, thereby improving the compatibility of the diatomite with organic substances or other inorganic substances.

[0017] The pretreated diatomaceous earth was dispersed in deionized water, and then FeCl3 solution was added. The pH value of the solution was adjusted to 1-3 by hydrochloric acid to ensure that the iron ions were in the appropriate form (such as Fe 3+ ) exists in the solution, and the iron ions are fully adsorbed on the surface and pores of diatomaceous earth. The iron ions can adsorb suspended matter, colloids and some soluble organic matter in the wastewater to form flocs that are easy to precipitate, thereby improving the adsorption capacity and selectivity of diatomaceous earth.

[0018] The treated diatomite is dispersed again in deionized water, and then sodium lignin sulfonate and starch are added. Sodium lignin sulfonate has good dispersion and stability, can absorb pollutants such as organic matter, color and turbidity in water, can exchange ions with water, adsorb and remove harmful ions, and sodium lignin sulfonate can be loaded in the diatomite structure as a coagulant to enhance the coagulation effect of diatomite and improve the removal rate of pollutants. Starch has a certain viscosity, which can make sodium lignin sulfonate firmly adhere to the surface and pores of diatomite, improve the removal efficiency of diatomite, and in addition, starch can increase the viscosity of wastewater, making solid particles in sewage easier to precipitate.

[0019] Diatomaceous earth, iron ions, sodium lignin sulfonate and starch are mixed and used in the treatment of printing and dyeing wastewater to form a synergistic effect. Diatomaceous earth and iron ions provide strong adsorption and coagulation capabilities, sodium lignin sulfonate acts as a coagulant to enhance the coagulation effect, and starch improves the treatment efficiency by increasing the viscosity of the wastewater and promoting the dissolution of dyes, thereby improving the dispersibility, stability and adsorption properties of diatomaceous earth.

[0020] Preferably, the mass ratio of the diatomaceous earth, sodium lignin sulfonate and starch is 1:0.4-0.6:0.1-0.2.

[0021] By adopting the above technical solution, the mass ratio of diatomite, sodium lignin sulfonate and starch is further limited within a certain range, and the modified diatomite obtained has a better comprehensive wastewater treatment effect. Diatomite has a high porosity and specific surface area, and adsorbs suspended matter, colloids and some soluble organic matter in wastewater. Sodium lignin sulfonate has good dispersibility and stability, and can disperse suspended matter and colloids in wastewater, load on the surface and pores of diatomite, and act as a coagulant aid of the coagulant to enhance the coagulation effect and improve the removal rate of pollutants.

[0022] Starch can increase the volume of suspended matter, dirt and other impurities in wastewater, making them easier to precipitate. Starch has a certain viscosity, which allows sodium lignin sulfonate to be stably loaded in the structure of diatomaceous earth, increasing the structural stability of modified diatomaceous earth. Both diatomaceous earth and sodium lignin sulfonate have strong adsorption capacity. The addition of starch can promote the precipitation of suspended matter and sludge dehydration in wastewater, thereby improving the efficiency and quality of wastewater treatment.

[0023] Preferably, the method for preparing the activated carbon filter layer comprises the following steps: (1) dispersing fibers, activated carbon particles, modified chitosan, and citric acid in deionized water, and stirring uniformly at a temperature of 60-65° C. to obtain a premix; (2) dipping the nonwoven fabric into the premix obtained in step (1) for 3-5 times, each dipping for 20-30 seconds, and drying after each dipping to obtain a core layer; (3) Laying a layer of non-woven fabric on both sides of the core layer of step (2), compacting and shaping at a temperature of 80-85° C. to obtain an activated carbon filter layer.

[0024] By adopting the above technical solution, the fiber plays the main role of structural support and filter medium in the activated carbon filter layer. The premix adheres to the non-woven fabric structure to form a filter layer with high-efficiency filtration performance, which can intercept suspended solids, colloids and some soluble organic matter in the wastewater, thereby reducing the turbidity and color of the wastewater. The activated carbon particles have a developed pore structure and a huge specific surface area, which can effectively adsorb organic dyes, heavy metal ions and other harmful substances in the wastewater, reduce the color and chemical oxygen demand (COD) in the wastewater, and improve the biodegradability of the wastewater.

[0025] Modified chitosan can form floccules with suspended matter, colloids, etc. in wastewater, accelerate their sedimentation and removal, and effectively adsorb dye molecules in wastewater, thereby reducing the chromaticity and turbidity of wastewater. In addition, modified chitosan has a certain viscosity, which makes the premix have good viscosity and can stably adhere to the non-woven fabric structure to form an effective filter layer. Citric acid adjusts the pH value of wastewater, optimizes the performance of other treatment agents, and improves the efficiency of wastewater treatment.

[0026] The premix obtained by dispersing fibers, activated carbon particles, modified chitosan and citric acid in deionized water forms a composite material with high efficiency filtration, adsorption and flocculation properties. The composite material adheres to the non-woven fabric to form an activated carbon filter layer, which effectively removes suspended matter, colloids, organic dyes and other harmful substances in wastewater through multiple mechanisms such as filtration, adsorption and flocculation, thereby reducing the turbidity, color and COD value of the wastewater and improving the biodegradability and discharge quality of the wastewater.

[0027] Preferably, the mass ratio of the fiber, activated carbon particles and modified chitosan is 1:0.7-0.8:0.5-0.6.

[0028] By adopting the above technical solution, the mass ratio of fiber, activated carbon particles and modified chitosan is further limited within a certain range, and the obtained mixture has a better adsorption effect. The fiber mainly plays a supporting and filtering role. The fiber can form a filter medium to remove large particle pollutants such as suspended matter and colloids in the wastewater by physical interception. The activated carbon particles effectively adsorb organic dyes, heavy metal ions and other harmful substances in the wastewater, load them on the surface and pores of the fiber, and improve the treatment efficiency of the fiber. Through the dual effects of physical adsorption and chemical adsorption, the activated carbon can significantly reduce the chromaticity and chemical oxygen demand (COD) in the wastewater and improve the biodegradability of the wastewater.

[0029] Modified chitosan has a certain viscosity, which allows the activated carbon particles to adhere stably to the fiber structure, and at the same time allows the premix to adhere to the non-woven fabric structure, increasing the fiber treatment efficiency. Moreover, modified chitosan can effectively adsorb dye molecules and additives in wastewater, reducing the color and turbidity of wastewater. The fiber, activated carbon particles and modified chitosan are mixed to form a synergistic effect. The fiber material, as a filter medium, can intercept large particle pollutants in the wastewater. Both activated carbon particles and modified chitosan have strong adsorption capacity and can adsorb organic dyes, heavy metal ions and other harmful substances in the wastewater. Modified chitosan can form floccules with suspended matter, colloids, etc. in the wastewater, accelerate their sedimentation and removal, and improve treatment efficiency.

[0030] Preferably, the preparation method of the modified chitosan comprises the following steps: adding chitosan to an ethanol aqueous solution with a volume concentration of 50-55%, adding sodium hydroxide solution, stirring at 65-70°C for 1-2h, adding chloroacetic acid and lauryl dimethylamine oxide, reacting at 40-45°C for 2-3h to obtain carboxymethyl chitosan; dispersing the carboxymethyl chitosan in deionized water, adding nanosilver particles and polyacrylamide, stirring for 3-4h, and drying to obtain modified chitosan.

[0031] By adopting the above technical scheme, sodium hydroxide solution is added to make chitosan swell under alkaline conditions to form an alkalinization center, chloroacetic acid and lauryl dimethylamine oxide are added, chloroacetic acid is used as a carboxylating agent, lauryl dimethylamine oxide is used as a catalyst, chitosan undergoes a carboxymethyl substitution reaction with chloroacetic acid under alkaline conditions to generate carboxymethyl chitosan, lauryl dimethylamine oxide participates in the catalytic regulation reaction process, and the obtained carboxymethyl chitosan has excellent adsorption performance and decolorization effect, can effectively adsorb organic matter in printing and dyeing wastewater, and improve the transparency and clarity of the wastewater.

[0032] Carboxymethyl chitosan is dispersed in deionized water to form a uniform solution, and nano-silver particles and polyacrylamide are added. The nano-silver particles are embedded in the carboxymethyl chitosan structure. The nano-silver particles have excellent antibacterial properties and can kill bacteria, viruses and other microorganisms in wastewater. Polyacrylamide has good film-forming properties and adhesion, which improves the viscosity of the chitosan system and helps to adhere to the structure of the non-woven fabric in the future, thereby improving the treatment effect of the non-woven fabric. Moreover, the mixed use of carboxymethyl chitosan and nano-silver particles can further enhance the adsorption effect on organic matter and heavy metal ions in wastewater, thereby improving the wastewater treatment efficiency. Polyacrylamide promotes the flocculation and precipitation of suspended matter and colloidal substances in wastewater, forms a synergistic effect with carboxymethyl chitosan and nano-silver particles, and accelerates the purification process of wastewater.

[0033] Preferably, the mass ratio of chitosan, nanosilver particles and polyacrylamide is 1:0.5-0.6:0.3-0.4.

[0034] By adopting the above technical scheme, the mass ratio of chitosan, nano-silver particles and polyacrylamide is further limited within a certain range, and the modified chitosan obtained has better comprehensive performance. Chitosan has excellent flocculation and adsorption properties, nano-silver particles have excellent antibacterial properties and catalytic activity, polyacrylamide has a good flocculation effect, and the mixture of chitosan, nano-silver particles and polyacrylamide has a synergistic effect. Nano-silver can be embedded in the chitosan structure, and polyacrylamide has a certain viscosity, which improves the viscosity of the chitosan system. Chitosan and polyacrylamide both have excellent flocculation properties. Mixing can further enhance the flocculation effect of wastewater and improve the removal rate of suspended matter and colloidal substances. The addition of nano-silver particles can improve the antibacterial properties of the wastewater treatment system, prevent microbial contamination and damage, and ensure the stability and reliability of wastewater treatment.

[0035] Preferably, the fiber is selected from one or more of polyester fiber, polypropylene fiber and polyamide fiber, and the fiber diameter is 200-300 μm.

[0036] By adopting the above technical scheme, polyester fiber, polypropylene fiber and polyamide fiber are used as supporting materials, carriers or reinforcing materials in the activated carbon filter layer, and have excellent physical and chemical stability, as well as good wear resistance and tear resistance. The main function is to increase the structural strength, surface area and filtration efficiency of the filter layer.

[0037] Preferably, the anaerobic bacteria treatment is carried out in an anaerobic tank.

[0038] By adopting the above technical solutions, the anaerobic tank is an important part of sewage treatment. It uses the action of anaerobic bacteria to remove organic matter in wastewater, improve the biodegradability of wastewater, and provide favorable conditions for subsequent treatment. The working principle of the anaerobic tank is mainly based on the metabolic activity of anaerobic bacteria. Under anaerobic conditions, anaerobic bacteria decompose organic matter in wastewater into methane, carbon dioxide, water, hydrogen sulfide, ammonia and other substances.

[0039] In summary, this application has the following beneficial effects: 1. In the present application, polyferric sulfate generates a large amount of positively charged iron ions after hydrolysis in water. These iron ions react electrically with negatively charged colloidal particles, suspended matter and some soluble organic matter in the printing and dyeing wastewater to form larger flocs, which settle rapidly under the action of gravity, thereby achieving the removal of pollutants in the wastewater.

[0040] 2. The modified diatomaceous earth in this application has high adsorption, large surface area and large porosity, and can adsorb pollutants such as heavy metals and organic matter in printing and dyeing wastewater. As an effective adsorbent, diatomaceous earth has a unique structure and purification effect, and can adsorb pigments in printing and dyeing wastewater and effectively remove chromaticity.

[0041] 3. In this application, the coagulation effect of polyferric sulfate and sodium aluminate can promote each other to form more stable and larger flocs and increase the sedimentation rate. The modified diatomaceous earth and polyferric sulfate further enhance the adsorption capacity of printing and dyeing wastewater, which helps to remove more pollutants. The mixed addition of polyferric sulfate, sodium aluminate and modified diatomaceous earth to printing and dyeing wastewater can give play to their respective advantages and synergistically improve the wastewater treatment efficiency. DETAILED DESCRIPTION

[0042] The present application is further described in detail below with reference to the embodiments.

[0043] The raw materials used in the examples and comparative examples can all be obtained commercially.

[0044] Preparation example of activated carbon filter layer Preparation Example 1-1 The method for preparing an activated carbon filter layer comprises the following steps: (1) dispersing 20 kg of fiber, activated carbon particles, modified chitosan, and 5 kg of citric acid in 70 kg of deionized water, and stirring at 63 ° C to obtain a premix; (2) dipping a non-woven fabric having a size of 2 m×2 m into the premix obtained in step (1), dipping 4 times, each dipping for 25 seconds, and drying after each dipping to obtain a core layer; (3) Laying a layer of non-woven fabric on both sides of the core layer of step (2), compacting and shaping at a temperature of 84° C. to obtain an activated carbon filter layer, wherein the thickness of the activated carbon filter layer is 30 mm.

[0045] The mass ratio of fiber, activated carbon particles and modified chitosan is 1:0.7:0.6.

[0046] The preparation method of modified chitosan comprises the following steps: adding 24 kg of chitosan to 450 L of ethanol aqueous solution with a volume concentration of 52%, adding sodium hydroxide, adjusting the system to a sodium hydroxide concentration of 15 wt%, stirring at 67 DEG C for 1.5 h, adding 50 kg of chloroacetic acid and 6 kg of lauryl dimethylamine oxide, reacting at 45 DEG C for 3 h to obtain carboxymethyl chitosan; dispersing the carboxymethyl chitosan in 80 L of deionized water, adding nano silver particles and polyacrylamide, stirring for 3.5 h, and drying to obtain modified chitosan.

[0047] The mass ratio of chitosan, nanosilver particles and polyacrylamide is 1:0.6:0.4.

[0048] The fibers were selected from polyester fibers and had a fiber diameter of 250 μm.

[0049] Preparation Example 1-2 The difference from Preparation Example 1-1 is that in step (1), no activated carbon particles are added.

[0050] Preparation Example 1-3 The difference from Preparation Example 1-1 is that in step (1), no modified chitosan is added.

[0051] Preparation Example 1-4 The difference from Preparation Example 1-1 is that the mass ratio of fiber, activated carbon particles and modified chitosan is 1:0.8:0.5.

[0052] Preparation Example 1-5 The difference from Preparation Example 1-1 is that the mass ratio of fiber, activated carbon particles and modified chitosan is 1:0.1:0.9.

[0053] Preparation Example 1-6 The difference from Preparation Example 1-1 is that in the preparation method of modified chitosan, no nano-silver particles are added.

[0054] Preparation Example 1-7 The difference from Preparation Example 1-1 is that no polyacrylamide is added in the preparation method of the modified chitosan.

[0055] Preparation Example 1-8 The difference from Preparation Example 1-1 is that in the preparation method of modified chitosan, the mass ratio of chitosan, nano-silver particles and polyacrylamide is 1:0.5:0.3.

[0056] Preparation Example 1-9 The difference from Preparation Example 1-1 is that in the preparation method of modified chitosan, the mass ratio of chitosan, nano-silver particles and polyacrylamide is 1:0.2:0.7. Example

[0057] Example 1 A printing and dyeing wastewater treatment process based on advanced oxidation technology comprises the following steps: (1) adding acid to 1 t of printing and dyeing wastewater to adjust the pH to 6, performing anaerobic bacteria treatment, filtering, and obtaining supernatant A; (2) adding the flocculant composition to the supernatant A of step (1), stirring for 6 hours, and filtering to obtain a supernatant B; (3) Add Fenton's reagent and potassium hydroxide solution to the supernatant B of step (2), adjust the pH value of the system to 6, mix and precipitate for 14 hours, and the amount of Fenton's reagent added is 0.07 kg / m 3 , filter using an activated carbon filter layer to obtain supernatant C, which is the standard discharge water; the mass concentration of the potassium hydroxide solution is 20%.

[0058] In the raw materials of the flocculant composition, the mass ratio of polyferric sulfate, sodium aluminate and modified diatomaceous earth is 2:1:4, wherein 100 g of sodium aluminate is added.

[0059] The preparation method of modified diatomite comprises the following steps: (1) 1 kg of diatomaceous earth was calcined at 470° C. for 3 h, then dispersed in 3 L of anhydrous ethanol, 0.3 kg of silane coupling agent KH-550 was added, stirred for 1.5 h, filtered and dried to obtain pretreated diatomaceous earth; (2) Disperse the diatomaceous earth pretreated in step (1) in 6 L of deionized water and add 2 L of 0.3 mol·L -1 FeCl3 solution, adjusting the pH value to 2 with hydrochloric acid, stirring at 84°C for 2.5h, standing for 24h, filtering, washing, and obtaining treated diatomaceous earth; (3) Disperse the treated diatomaceous earth in step (2) in 10 L of deionized water, add sodium lignin sulfonate and starch, stir at 65° C. for 2 h, filter, and dry to obtain modified diatomaceous earth.

[0060] The mass ratio of diatomaceous earth, sodium lignin sulfonate and starch is 1:0.4:0.1.

[0061] Anaerobic bacteria treatment is carried out in an anaerobic tank.

[0062] The activated carbon filter layer was purchased from commercial sources.

[0063] Example 2 A printing and dyeing wastewater treatment process based on advanced oxidation technology, which differs from Example 1 in that it comprises the following steps: (1) adding acid to 1 t of printing and dyeing wastewater to adjust the pH to 7, performing anaerobic bacteria treatment, filtering, and obtaining supernatant A; (2) adding the flocculant composition to the supernatant A of step (1), stirring for 4 hours, and filtering to obtain a supernatant B; (3) Add Fenton's reagent and potassium hydroxide solution to the supernatant B of step (2), mix and precipitate for 12 hours, and the amount of Fenton's reagent added is 0.08 kg / m 3 , filter using an activated carbon filter layer to obtain supernatant C, which is the standard discharge water; In the raw materials of the flocculant composition, the mass ratio of polyferric sulfate, sodium aluminate and modified diatomaceous earth is 1.5:1:7.

[0064] In the preparation method of modified diatomaceous earth, the mass ratio of diatomaceous earth, sodium lignin sulfonate and starch is 1:0.6:0.2.

[0065] Example 3 A printing and dyeing wastewater treatment process based on advanced oxidation technology, which is different from Example 1 in that the mass ratio of polyferric sulfate, sodium aluminate and modified diatomaceous earth is 0.1:1:13.

[0066] Example 4 A printing and dyeing wastewater treatment process based on advanced oxidation technology, which is different from Example 1 in that the mass ratio of diatomaceous earth, sodium lignin sulfonate and starch is 1:0.1:0.5.

[0067] Example 5 A printing and dyeing wastewater treatment process based on advanced oxidation technology, which is different from Example 1 in that the activated carbon filter layer comes from Preparation Example 1-1.

[0068] Example 6 A printing and dyeing wastewater treatment process based on advanced oxidation technology, which is different from Example 1 in that the activated carbon filter layer comes from Preparation Example 1-2.

[0069] Example 7 A printing and dyeing wastewater treatment process based on advanced oxidation technology, which is different from Example 1 in that the activated carbon filter layer comes from Preparation Example 1-3.

[0070] Example 8 A printing and dyeing wastewater treatment process based on advanced oxidation technology, which is different from Example 1 in that the activated carbon filter layer comes from Preparation Examples 1-4.

[0071] Example 9 A printing and dyeing wastewater treatment process based on advanced oxidation technology, which is different from Example 1 in that the activated carbon filter layer comes from Preparation Example 1-5.

[0072] Example 10 A printing and dyeing wastewater treatment process based on advanced oxidation technology, which is different from Example 1 in that the activated carbon filter layer comes from Preparation Example 1-6.

[0073] Embodiment 11 A printing and dyeing wastewater treatment process based on advanced oxidation technology, which is different from Example 1 in that the activated carbon filter layer comes from Preparation Example 1-7.

[0074] Example 12 A printing and dyeing wastewater treatment process based on advanced oxidation technology, which is different from Example 1 in that the activated carbon filter layer comes from Preparation Example 1-8.

[0075] Embodiment 13 A printing and dyeing wastewater treatment process based on advanced oxidation technology, which is different from Example 1 in that the activated carbon filter layer comes from Preparation Example 1-9.

[0076] Embodiment 14 A printing and dyeing wastewater treatment process based on advanced oxidation technology is different from Example 1 in that sodium lignin sulfonate is not added in the preparation method of modified diatomaceous earth.

[0077] Embodiment 15 A printing and dyeing wastewater treatment process based on advanced oxidation technology is different from Example 1 in that starch is not added in the preparation method of modified diatomaceous earth.

[0078] Comparative Example Comparative Example 1 A printing and dyeing wastewater treatment process based on advanced oxidation technology, which differs from Example 1 in that no polyferric sulfate is added.

[0079] Comparative Example 2 A printing and dyeing wastewater treatment process based on advanced oxidation technology, which differs from Example 1 in that sodium aluminate is not added.

[0080] Comparative Example 3 A printing and dyeing wastewater treatment process based on advanced oxidation technology, which differs from Example 1 in that modified diatomaceous earth is not added.

[0081] Comparative Example 4 A printing and dyeing wastewater treatment process based on advanced oxidation technology, which differs from Example 1 in that the modified diatomaceous earth is replaced by an equal amount of diatomaceous earth.

[0082] Performance testing The printing and dyeing wastewater treatment process based on advanced oxidation technology prepared in Examples 1-15 and Comparative Examples 1-4 was subjected to performance tests, COD was detected with reference to HJ-T 399-2007 "Determination of Chemical Oxygen Demand of Water Quality - Rapid Digestion Spectrophotometry", chromaticity was detected with reference to GB11903-1989 "Determination of Chroma of Water Quality", total nitrogen was detected with reference to HJ 636-2012 "Determination of Total Nitrogen of Water Quality - Alkaline Potassium Persulfate Digestion Ultraviolet Spectrophotometry", ammonia nitrogen was detected with reference to HJ 535-2009 "Determination of Ammonia Nitrogen of Water Quality - Nessler's Reagent Spectrophotometry", and suspended matter was detected with reference to "Determination of Suspended Matter in Water Quality - Gravimetric Method GB11901-89", and the test results are shown in Table 1.

[0083] Table 1 Test data of embodiments and comparative examples As can be seen from Table 1, Examples 1-2 of the present application have good treatment effects on printing and dyeing wastewater, wherein the COD removal rate of Example 1 is 93.1%, the chromaticity removal rate is 93.9%, the total nitrogen removal rate is 92.0%, the ammonia nitrogen removal rate is 95.0%, and the suspended matter removal rate is 95.1%. This indicates that the flocculant composition in the present application enhances the adsorption capacity of printing and dyeing wastewater, helps to remove more pollutants, and cooperates with the activated carbon filter layer for effective filtration, further improving the removal efficiency of various pollutants.

[0084] Example 3 changes the mass ratio of polyferric sulfate, sodium aluminate, and modified diatomite, and comparative examples 1-3 do not add polyferric sulfate, sodium aluminate, and modified diatomite, respectively, and comparative example 4 replaces the modified diatomite with an equal amount of diatomite. As can be seen from Table 1, the test results of COD removal rate, chromaticity removal rate, total nitrogen removal rate, ammonia nitrogen removal rate, and suspended solids removal rate of Example 3 are significantly worse than those of Example 1-2, and the corresponding test results of Comparative Examples 1-4 are significantly worse than those of Example 1-3, indicating that the synergistic effect of modified diatomite with polyferric sulfate and sodium aluminate improves the treatment efficiency of wastewater, and has significant coagulation, decolorization, organic matter removal, phosphorus removal, adsorption and neutralization effects, and these effects cooperate with each other to jointly improve the treatment efficiency and treatment effect of printing and dyeing wastewater; moreover, the corresponding performance test effect of Comparative Example 4 is better than that of Comparative Example 3, but worse than that of Examples 1-3 and Comparative Examples 1-2, indicating that the diatomite modified by the present application has excellent adsorption performance and pollutant removal efficiency.

[0085] Example 4 changes the mass ratio of diatomite, sodium lignin sulfonate and starch, and sodium lignin sulfonate and starch are not added in the preparation method of modified diatomite in Examples 14-15. As can be seen from Table 1, the test results of COD removal rate, chromaticity removal rate, total nitrogen removal rate, ammonia nitrogen removal rate and suspended matter removal rate of Example 4 are significantly worse than those of Examples 1-2, while the corresponding test results of Examples 14-15 are worse than those of Example 4, indicating that starch has a certain viscosity, so that sodium lignin sulfonate can be stably loaded in the structure of diatomite, increasing the structural stability of modified diatomite, diatomite and sodium lignin sulfonate both have strong adsorption capacity, and the addition of starch can promote the precipitation of suspended matter and sludge dehydration in wastewater, thereby improving the efficiency and quality of wastewater treatment.

[0086] The activated carbon filter layer in Example 5 was prepared by the preparation method of the present application. As can be seen from Table 1, the test results of its COD removal rate, chromaticity removal rate, total nitrogen removal rate, ammonia nitrogen removal rate, and suspended matter removal rate are significantly better than those of Examples 1-2, and its comprehensive test performance is greatly improved, indicating that the flocculant composition used in the present application is combined with the homemade activated carbon filter layer to effectively remove suspended matter, colloids, organic dyes and other harmful substances in the wastewater, thereby reducing the turbidity, chromaticity and COD value of the wastewater, and improving the biodegradability and discharge quality of the wastewater.

[0087] In the preparation method of the activated carbon filter layer of Examples 6-7, activated carbon particles and modified chitosan are not added respectively. In Examples 8-9, the mass ratio of fibers, activated carbon particles and modified chitosan is changed. As can be seen from Table 1, the test results of COD removal rate, chromaticity removal rate, total nitrogen removal rate, ammonia nitrogen removal rate and suspended solids removal rate of Examples 6-7 are significantly worse than those of Examples 5 and 8, but better than those of Examples 1-2. The corresponding performance test results of Example 9 are significantly better than those of Examples 6-7 and 1-2, but worse than those of Example 5, indicating that the modified chitosan has a certain viscosity, so that the activated carbon particles can be stably adhered to the fiber structure, and the premix can be adhered to the non-woven fabric structure. Both the activated carbon particles and the modified chitosan have strong adsorption capacity, which can adsorb organic dyes, heavy metal ions and other harmful substances in wastewater. The modified chitosan can form floccules with suspended matter, colloids, etc. in the wastewater, accelerate their sedimentation and removal, and improve the treatment efficiency.

[0088] In the preparation method of modified chitosan in Examples 10-11, nanosilver particles and polyacrylamide are not added respectively. In Examples 12-13, the mass ratio of chitosan, nanosilver particles and polyacrylamide is changed. It can be seen from Table 1 that the test results of COD removal rate, chromaticity removal rate, total nitrogen removal rate, ammonia nitrogen removal rate and suspended solids removal rate of Examples 10-11 are significantly better than those of Examples 6-7, but worse than those of Examples 5 and 12. The corresponding performance test results of Example 13 are significantly better than those of Examples 10-11, but worse than those of Examples 5 and 12, indicating that the mixture of chitosan, nanosilver particles and polyacrylamide has a synergistic effect, nanosilver can be embedded in the chitosan structure, polyacrylamide has a certain viscosity, and improves the viscosity of the chitosan system. Both chitosan and polyacrylamide have excellent flocculation properties, and mixed use can further enhance the flocculation effect of wastewater and improve the removal rate of suspended solids and colloidal substances. The addition of nanosilver particles can improve the antibacterial performance of the wastewater treatment system, prevent microbial contamination and damage, and ensure the stability and reliability of wastewater treatment.

[0089] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A printing and dyeing wastewater treatment process based on advanced oxidation technology, characterized in that: The steps include: (1) Acid is added to the printing and dyeing wastewater to adjust the pH to between 6 and 7, and then anaerobic bacteria treatment is performed, and the wastewater is filtered to obtain supernatant A; (2) adding the flocculant composition to the supernatant A of step (1), stirring for 4-6 hours, and filtering to obtain supernatant B; (3) Add Fenton's reagent and alkali solution to the supernatant B of step (2), mix and precipitate for 12-14 hours, and the amount of Fenton's reagent added is 0.07-0.08 kg / m 3 , filter using an activated carbon filter layer to obtain supernatant C, which is the standard discharge water; The raw materials of the flocculant composition are polyferric sulfate, sodium aluminate and modified diatomaceous earth.

2. A printing and dyeing wastewater treatment process based on advanced oxidation technology according to claim 1, characterized in that: The mass ratio of the polymerized ferric sulfate, sodium aluminate and modified diatomaceous earth is 1.5-2:1:4-7.

3. A printing and dyeing wastewater treatment process based on advanced oxidation technology according to claim 1, characterized in that: The preparation method of the modified diatomite comprises the following steps: (1) calcining diatomite at 450-480°C for 2-3h, dispersing it in anhydrous ethanol, adding silane coupling agent KH-550, stirring for 1-2h, filtering and drying to obtain pretreated diatomite; (2) Dispersing the diatomaceous earth pretreated in step (1) in deionized water, adding FeCl3 solution, adjusting the pH value to 1-3 with hydrochloric acid, stirring at 80-85°C for 2-3h, standing for 20-24h, filtering, washing, and obtaining treated diatomaceous earth; (3) Disperse the treated diatomaceous earth in step (2) in deionized water, add sodium lignin sulfonate and starch, stir at a temperature of 60-65° C. for 1-2 h, filter, and dry to obtain modified diatomaceous earth.

4. A printing and dyeing wastewater treatment process based on advanced oxidation technology according to claim 3, characterized in that: The mass ratio of the diatomaceous earth, sodium lignin sulfonate and starch is 1:0.4-0.6:0.1-0.

2.

5. The printing and dyeing wastewater treatment process based on advanced oxidation technology according to claim 1 is characterized in that: The method for preparing the activated carbon filter layer comprises the following steps: (1) Dispersing fibers, activated carbon particles, modified chitosan, and citric acid in deionized water, stirring uniformly at a temperature of 60-65° C. to obtain a premix; (2) dipping the non-woven fabric into the premix obtained in step (1) for 3-5 times, each time for 20-30 seconds, and drying after each dipping to obtain a core layer; (3) Lay a layer of non-woven fabric on both sides of the core layer in step (2), compact and shape at a temperature of 80-85°C to obtain an activated carbon filter layer.

6. A printing and dyeing wastewater treatment process based on advanced oxidation technology according to claim 5, characterized in that: The mass ratio of the fiber, the activated carbon particles and the modified chitosan is 1:0.7-0.8:0.5-0.

6.

7. A printing and dyeing wastewater treatment process based on advanced oxidation technology according to claim 5, characterized in that: The preparation method of the modified chitosan comprises the following steps: adding chitosan to an ethanol aqueous solution with a volume concentration of 50-55%, adding a sodium hydroxide solution, stirring at 65-70°C for 1-2h, adding chloroacetic acid and lauryl dimethylamine oxide, reacting at 40-45°C for 2-3h to obtain carboxymethyl chitosan; dispersing the carboxymethyl chitosan in deionized water, adding nano silver particles and polyacrylamide, stirring for 3-4h, and drying to obtain the modified chitosan.

8. A printing and dyeing wastewater treatment process based on advanced oxidation technology according to claim 7, characterized in that: The mass ratio of the chitosan, the nano-silver particles and the polyacrylamide is 1:0.5-0.6:0.3-0.

4.

9. A printing and dyeing wastewater treatment process based on advanced oxidation technology according to claim 5, characterized in that: The fiber is selected from one or more of polyester fiber, polypropylene fiber and polyamide fiber, and the fiber diameter is 200-300 μm.

10. The printing and dyeing wastewater treatment process based on advanced oxidation technology according to claim 1, characterized in that: The anaerobic bacteria treatment is carried out in an anaerobic tank.

Citation Information

Patent Citations

  • Flocculating agent for textile sewage

    CN104291424A

  • Treatment method of textile wastewater

    CN105692952A

  • Method for printing and dyeing wastewater purification treatment in different steps

    CN108467156A

  • Preparation of resin microspheres of resin microspheres in printing and dyeing wastewater treatment and application thereof

    CN111514865A

  • Printing and dyeing wastewater treatment process

    CN117209094A